Non-Hodgkin lymphoma risk and organophosphate and carbamate insecticide use in the north American pooled project - Stella Koutros; Shelley A. Harris; John J. Spinelli; Aaron Blair; John R. McLaughlin; Shelia Hoar Zahm; Sungduk Kim; Paul S. Albert; Linda Kachuri; Manisha Pahwa; Kenneth P. Cantor; Dennis D. Weisenburger; et al. (Environment International, 2019)
Organophosphates and carbamates have been among the most commonly used insecticides, with both agricultural and residential uses. Previous studies have suggested associations of non-Hodgkin lymphoma (NHL) with some of these chemicals; however, many studies have been limited in their ability to evaluate associations with lymphoma subtypes. We evaluated the use of eleven organophosphate and two carbamate insecticides in association with NHL in the North American Pooled Project, which includes data from case-control studies in the United States and Canada (1690 cases/5131 controls). We used unconditional logistic regression adjusting for potential confounders, including use of other pesticides, to estimate odds ratios (OR) and 95% confidence intervals (CI) for associations between these chemicals and NHL overall, and NHL subtypes, i.e., follicular (FL), diffuse large B-cell (DLBCL), small lymphocytic lymphoma (SLL) and others. Ever use of malathion was associated with increased risk of NHL overall (OR = 1.43; 95% CI: 1.14–1.81) compared with never users. Categories using tertiles of duration (<4 yrs., 4–12 yrs., and >12 yrs) also showed a significant exposure-response for increasing years of use of malathion and risk of NHL (OR<4vsUnex = 1.33 (0.88, 2.03), OR4-12vsUnex = 1.42 (1.02, 1.96), OR>12vsUnex = 1.55 (1.05, 2.28, p-trend < 0.01)). In addition, malathion use was statistically significantly associated with FL (OR = 1.58; 95% CI: 1.11–2.27) and DLBCL (OR = 1.61; 95% CI: 1.16–2.22) while there were no apparent associations with SLL or other subtypes, the p-value for heterogeneity across subtypes, however, was not significant. These results support previous studies suggesting an association between insecticide use and NHL overall, and provide new information on associations with NHL subtypes.